Urethral Mobility Ultrasound: A Comparable Diagnostic Method for Urethral Hypermobility in Indonesian Women with Stress Urinary Incontinence - Hidayah, Gita Nurul; Hidayat, Fery; Angelina, Jessica; Moegni, Fernandi (eJournal Kedokteran Indonesia, 2025)
Urethral hypermobility is the primary mechanism of stress urinary incontinence. In Indonesia, the prevalence of SUI (stress urinary incontinence) is approximately 13% (the other 16% had mixed urinary incontinence). To diagnose urethral hypermobility, the Q-tip test is performed, but it can provoke discomfort. Urethral mobility ultrasonography (UMU) has emerged as a non-invasive, more comfortable alternative, with high accuracy. This study reports the concordance of the evaluations in Indonesian women with SUI, to evaluate the accuracy of UMU compared with the Q-tip test in diagnosing urethral hypermobility among Indonesian women with SUI. A cross-sectional study was conducted at the outpatient clinic of RSUPN Dr Cipto Mangunkusumo and at the Jakarta Urogynecology (JUN) Centre-YPK Mandiri Hospital during the January – December 2024 period. Thirty-six SUI women without symptomatic pelvic organ prolapse (POP) completed the study. Each subject underwent a Q-tip test and ultrasonographic evaluation of urethral mobility. Ultrasonographic assessment of urethral mobility demonstrated high sensitivity (92.6%) but low specificity (33.3%) compared to the Q-tip test. The positive predictive value (PPV) of UMU was 80.6%, while the negative predictive value (NPV) was 60%. The concordance value was 77.8%. 16.67% of patients reported discomfort and pain during the Q-tip test and required medication to manage their symptoms. In those women, the Qtip test was negative but may reflect bias/false negatives, which can affect ultrasound specificity. With 80.6% PPV, 60% NPV, and 77.8% concordance, UMU may serve as a practical alternative to the Q-tip test in daily clinical practice.